PELATIHAN DAN SOSIALISASI SISTEM INFORMASI KEUANGAN PADA SEKOLAH ISLAM TERPADU PEKANBARU - Wenni Syafitri; Muhamad Sadar; Eddisyah Putra Pane (Universitas Lancang Kuning, 2018)
SMP IT Madani as one of the schools that apply the concept of islamic in its education practice. SMPIT Madani is a school formed by amil zakat self-supporting institution ummah Riau by using theconcept of free school. SMP IT stands in 2011 with a total of 20 students. Over time, the currentnumber of junior Madani IT students amounted to 75 students. The average students who attendjunior high school IT is the students who come from poor families.SMP IT Madani has received School Operational Assistance (BOS) a few years back. The BOSprogram uses a different approach than Special Assistance for Students (BKM) ie BOS funds are notgiven to poor students but are provided to schools and managed by schools. The mechanism forcalculating BOS funds is based on the number of students in each school. So the goal of this BOScan be achieved is to free the cost of education for poor students or not able and can alleviate forother students so they can get 9 years basic education services.The obligations of schools receiving BOS programs should report the realization of the use of theprogram to the government. Currently schools are having difficulties to make reporting realizationof BOS program to government and foundation. Differences in reporting formats to foundations andgovernments make the school experience serious problems. If it does not sync between reportingbetween the government and the foundation will cause many other questions and problems. Wheninterviewed, the school is very eager for this matter to be resolved immediately.Based on the problems of the partners, it can be concluded the solution of the problem is a reportinginformation system synchronized to the government and the foundation. So that SMP IT Madani nolonger experience obstacles to the reporting of BOS program activities. As a result the name ofUnilak increasingly fragrant in the eyes of society, especially SMP IT Madani.Method of implementation of activities used is direct observation to the location of partners toperform the first phase, this stage includes data collection and data processing. When this stage takesplace, we will get an overview of the Information Technology environment, and the partner's needfor the BOS program reporting mechanism. After the first phase is done, it will be held the secondphase of socialization, this stage to do the sosiasisasi about the benefits of synchronizing BOSreporting to the government and the foundation. Then in the third stage, the authors do the designand implementation of BOS reporting system based on information obtained from the foundation.Finally, the training phase: Each partner school sends its representative two people, to attend trainingon the use of reporting system that can synchronize BOS and foundation reporting.